Grammatical Error of Arabic Language in Student Thesis Department of Education Arabic Language FBPS UPI/ Kesalahan Nahwu Bahasa Arab Dalam Skripsi Mahasiswa Departemen Pendidikan Bahasa Arab FBPS UPI - Nurbayan, Dedeng Rosyidin; Nurbayan, Yayan; Falah, Kurnia Nurul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
This research is an overview of the grammatical aspects of / Nahwu and their mistakes in the Department of Arabic Language Education FPBS UPI's thesis. The description aims to describe the form of Nahwu errors in the student thesis. The method used is descriptive with a content analysis approach—research data collected through documentation. The object of the problem studied is the aspects of nahwu and its errors in the 2012-2015 graduate students' thesis. The collected data is analyzed quantitatively and qualitatively to reach the node. The results of the study obtained were 89 grains of nahwu. Based on position and i'rab, the error consists of marfu'at, manshubat and majrurat. As for the wording, errors consist of murakkab idhafi, murakkab washfi, and murakkab isnadi. Meanwhile, according to the type of sentence, the error consists of the number of ismiyah, number of fi'liyah, and syibhul amount. Nahwu errors generally stem from limitations in understanding and using nahwu rules in writing. This research is recommended for Arabic lecturers and students. This research is expected to be beneficial for improving and developing the quality of the Arabic thesis preparation